UAE experience in transitioning towards a green economy - Oanan, Mai (The Gulf Economist, 2023)
The world has witnessed a major shift in the environmental arena as a result of climate change, water scarcity ,desertification and gas emissions .The experience of the United Arab Emirates was chosen. The indicators have also been applied to identify the possibilities of transformation towards a green economy , and to identify the most important obstacles that prevent the possibility of transformation . Real growth achieved through economic policies to preserve the ecosystem .